An investigation of the impact of selected cooling strategies on milling of difficult-to-cut materials with an emphasis on titanium alloys and hardened steel - Hammond, Derek (Stellenbosch : Stellenbosch University, 2013)
Thesis (MScEng)--Stellenbosch University, 2013.